2014
DOI: 10.1186/1752-1947-8-30
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured aneurysm at the fenestration of the middle cerebral artery detected by magnetic resonance angiography in a patient with systemic lupus erythematosus and renal failure: a case report

Abstract: IntroductionA cerebral aneurysm arising at the fenestration of the middle cerebral artery is extremely rare, with one report describing subarachnoid hemorrhage due to this type of lesion. There have been no reports of this type of lesion occurring in a patient with systemic lupus erythematosus.Case presentationA 47-year-old Japanese woman with 23 years’ history of systemic lupus erythematosus and chronic renal failure had sudden onset of subarachnoid hemorrhage. We avoided using contrast medium due to her chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Our extensive review found 11 reported cases of DOMAassociated aneurysms, including ours. [3,5,7,[9][10][11][12][18][19][20] e paucity may be, in part, due to the general lack of awareness of this variation. Actually, out of the 11 patients, five were reported as fenestration in MCA and three as MCA duplication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our extensive review found 11 reported cases of DOMAassociated aneurysms, including ours. [3,5,7,[9][10][11][12][18][19][20] e paucity may be, in part, due to the general lack of awareness of this variation. Actually, out of the 11 patients, five were reported as fenestration in MCA and three as MCA duplication.…”
Section: Discussionmentioning
confidence: 99%
“…So far as we know, there are 11 reported patients, including ours, eight women and three men, with an aneurysm arising from DOMA [Table 1]. [3,5,7,[9][10][11][12][18][19][20] e age ranged from 42 to 81 years old with a mean of 54.8 ± 13.4 (Standard deviation [SD]) years. Our patient is the youngest.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies reporting of 12 patients were identified, aging from 14 to 81 (49.3 ± 13.1) years old ( Table 3) (2,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). The male to female ratio was 1:1.…”
Section: Mca Fenestration Aneurysmmentioning
confidence: 99%
“…Twelve studies reporting of 12 patients were identi ed, aging from 14 to 81 (49.3 ± 13.1) years old (Table 3) [2,[48][49][50][51][52][53][54][55][56][57][58]. The male to female ratio was 1:1.…”
Section: Mca Fenestration Aneurysmmentioning
confidence: 99%